Polynomial Reproduction of Vector Subdivision Schemes - Y. F. Shen; D. H. Yuan; S. Z. Yang (Abstract and Applied Analysis)
We discuss the polynomial reproduction of vector subdivision schemes with general integer dilation m≥2. We first present a simple algebraic condition for polynomial reproduction of such schemes with standard subdivision symbol. We then extend it to general subdivision symbol satisfying certain order of sum rules. We also illustrate our results with several examples. Our results show that such kind of scheme can produce exactly the same scalar polynomial from which the data is sampled by convolving with a finite nonzero sequence of vectors.